PENGALAMAN BERAGAMA SUFI JALALUDDIN RUMI DALAM PERSPEKTIF PSIKOLOGI - Hajriansyah, Hajriansyah (Jurnal Ilmu Ushuluddin, 2015)
Sufiâs poetry or the poetry of Islamic Mysticism is part of the cultural heritage of Islam. If the mention of the manyÂ names of Sufi poets, the most commonly known and easily referred to is the name of Maulana Jalaluddin Rumi orÂ Rumi. This writing wants to frame the religious experience of Rumi, through his poetries that reflects the attitude ofÂ Sufiâs doctrine, in the perspective of Sufi psychologhy. The conclusion was obtained that Rumi was from the type ofÂ prophetic religion, so that his attitude of the religion did not leave Syariat aspects which part of Islamic doctrine,Â although he put a lot of mystical attitude in his eccentric poems since his meeting with Syams Tabriz.